Genetic evidence for shared mechanisms of epimorphic regeneration in zebrafish - Qin, Zhao (National Academy of Sciences, 2009)
In a microarray-based gene profiling analysis of Müller glia-derived retinal stem cells in light-damaged retinas from adult zebrafish, we found that 2 genes required for regeneration of fin and heart tissues in zebrafish, hspd1 (heat shock 60-kDa protein 1) and mps1 (monopolar spindle 1), were up-regulated. Expression of both genes in the neurogenic Müller glia and progenitors was independently verified by quantitative reverse transcriptase PCR and in situ hybridization. Functional analysis of temperature-sensitive mutants of hspd1 and mps1 revealed that both are necessary for Müller glia-based cone photoreceptor regeneration in adult zebrafish retina. In the amputated fin, hspd1 is required for the induction of mesenchymal stem cells and blastema formation, whereas mps1 is required at a later step for rapid cell proliferation and outgrowth. This temporal sequence of hspd1 and mps1 function is conserved in the regenerating retina. Comparison of gene expression profiles from regenerating zebrafish retina, caudal fin, and heart muscle revealed additional candidate genes potentially implicated in injury-induced epimorphic regeneration in diverse zebrafish tissues.